“Construcción de un colector cilíndrico parabólico autónomo con Arduino para obtener agua caliente” - Macías Moreno, José Ignacio (2020)
The project consists on the construction of a parabolic cylindrical collector prototype with Arduino to obtain hot water for domestic usage, taking advantage of the solar energy through the incident radiation on the reflective base that drives the sun ray towards the manifold that is in charged to absorb the thermal energy that is driven towards the storage tank where the heat is transferred through copper tube. Before the construction of the solar parabolic solar collector. The data of the solar radiation in Canton La Mana was obtained, having as average 3,87KWh/m2/ day in 2018, retrieved from the NASA web site. That radiation is in the range of work of systems of low temperature with heat tubes. For the monitoring of the temperature in function of the time the measurement was done with a termopar K type industrial sensor, which is connected to the control card MAX6675. It makes the compensation and linearization of the sensor reply with a ADC in such a way that it is compatible with the Arduino card, which registers the data of the temperature and permit its visualization on the LCD screen, expressed in Celsius degrees. On the tests of the cylindrical parabolic collector it was obtained a temperature of 54,3ºC with a maximum radiation of 1,030kWh/m2, reaching a performance of 17,9% ion function of the useful energy for the warming of water with a contribution to the environment as this system of warming dos not produce emanations of CO2 to the atmosphere.